Penguatan Profil Pelajar Pancasila Melalui Pembelajaran Bahasa Indonesia Materi Cerita Pendek di Sekolah Dasar - Najati, Nida Aulia; Mahfud, Hasan; Yulisetiani, Septi (Jurnal Pendidikan Dasar, 2023)
This research describes strengthening the profile of Pancasila students by using alternative Indonesian language learning short story materials that are applied at SDN Totosari No.102 Surakarta.. The research method used is descriptive qualitative. The subjects of this study were students of grade IV and teachers of grade IV. Data collection techniques used are observation, interviews, and documentation studies. The data analysis techniques used are 1) Data Reduction, 2) Data Presentation, 3) Conclusion Drawing. Through this research, it is possible to see the application of short story learning material used in teaching and learning activities to reinforce values in the Pancasila student profile for fourth grade students especially in Indonesia language lesson with short story material. Kata kunci: Pancasila student profile, Indonesian language subjects, short story